Urethrovaginal space during the third trimester of pregnancy is not related to vaginal orgasm: Urethrovaginal space, pregnancy and vaginal orgasm - Sisti, Giovanni; Cozzolino, Mauro; Sorbi, Flavia; Oranges, Carlo Maria; Pachon Romero, Maria Isabel; Landi, Riccardo; Sisti, Andrea; Fambrini, Massimiliano (Acta Biomedica Atenei Parmensis, 2019)
Introduction: Sexologists have described the urethrovaginal space (UVS) as a region of the body involved in the female orgasm. Recently certain authors have described the UVS via ultrasound (US). Pregnancy is associated with a myriad of physiological, anatomical and biochemical changes. To measure the UVS thickness in the third trimester of pregnancy and to investigate the relationship between the UVS thickness and the presence of vaginal orgasm. Material and Methods: Sexually active pregnant patients in the third trimester were included. We measured the UVS via US. Each patient compiled a modified female sexual function index (FSFI) questionnaire and was categorized in group with or without vaginal orgasm. Association between vaginal orgasm and UVS thickness was evaluated via t-test and ROC curve analysis. Results: UVS thickness resulted greater than 15 mm (average) in the third trimester, and was not related to the presence of vaginal orgasm (p>0.05). Conclusion: UVS thickness is high in the third trimester of pregnancy but it is not related to the presence of vaginal orgasm.